Utilization of Green Betel Leaf as Adsorbent of Lead and Copper Metals in Artificial Wastewater - Syahrir, Muallim; Yasser, M; Rosalin, Rosalin (Politeknik Negeri Ujung Pandang, 2023)
Green betel leaf contains phenolic compounds that can bind metal ions. The purpose of this study was to determine the effect of variations in the mass of green betel leaf and stirring time based on the efficiency and adsorption capacity of lead and copper metals in artificial wastewater. Adsorption process using the stirring with a magnetic stirrer. The variation used is the stirring time of 30 and 60 minutes and the mass of the adsorbent is 25,30,35, 40 grams. Artificial wastewater is made from 1 gram of each Pb(NO3)2 and CuCl2.2H20 in 500 ml of aquadest. Analysis of the metal using the AAS (Atomic Absorption Spectrophotometry). The results of the analysis showed that the optimum adsorption of lead metal was at a mass of 30 grams of betel leaf and a stirring time of 1 hour, where green betel leaves were able to adsorb 99.96% of lead metal, from a Pb level of 6435 ppm to 2.48 ppm. While the optimum results for adsorption of copper metal were 35 grams of betel leaf mass and 30 minutes of stirring time, where green betel leaves were able to adsorb 49.83% copper metal, from 158 ppm Cu level to 79.27 ppm.